Kualitas Produk, Kualitas Layanan, dan Harga terhadap Kepuasan Pelanggan - Mamik Kusuma Ningrum; Trias Setyowati; Wenny Murtaliningtyas (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine and analyze the effect of product quality, service quality, and price on customer satisfaction. This research method is descriptive quantitative. The sample used in this study was 90 respondents using purposive sampling method. The analytical tool used to analyze product quality, service quality, and price on customer satisfaction is multiple linear regression using the SPSS statistical program for window.v.26. The results showed, a) the quality of the product had a significance level of 0.457 and a positive positive regression coefficient of 0.044; b) service quality has a significance level of 0.004 and a positive feasible regression coefficient of 0.214; c) customer satisfaction has a significance level of 0.000 and a positive feasible regression coefficient of 0.343. In conclusion, product quality has a positive and insignificant effect on customer satisfaction, service quality has a positive and significant effect on customer satisfaction, and price has a positive effect on customer satisfaction. Keywords: product quality, service quality, price and customer satisfaction